MANFAAT MOBILISASI DAN MASASE PADA PASIEN STROKE DI DUSUN 3 DESA SELAMAT KECAMATAN SIBIRU-BIRU KABUPATEN DELI SERDANG - Hariati, Hariati; Hutabarat, Vitrilina; Riyanto, Riyanto; Zuliawati, Zuliawati; Sinaga, Jon Piter (INSTITUT KESEHATAN DELI HUSADA, 2024)
Stroke is a disease that can cause disability in sufferers. To prevent this disability, mobilization and massage can be carried out. In connection with the high stroke disability in Dusun III, Selamat Village, it is necessary to provide counseling on the Benefits of Mobilization and Massage for Stroke Patients. The action provides passive exercise to maintain the physiological function of muscles and joints in patients who undergo long-term bed rest. Mobilization exercises should be carried out as soon as possible to prevent complications due to lack of physical activity, such as contractures and joint stiffness. Meanwhile, massage is a rubbing technique using the palms, fingers, or back of the hand, which follows the blood flow towards the heart with adjusted pressure. This technique is useful for relaxing muscles and nerve endings, as well as improving blood circulation. The benefits of this community service activity are that residents of Dusun III, Selamat Village better understand how to prevent disability in stroke patients by carrying out mobilization and massage to improve the quality of life of stroke patients.